THE STUDENTS’ DIFFICULTIES FACTORS IN SPEAKING - Santi Andriani Putri; Samsul Amri; Ahmad Ahmad (J-Shelves of Indragiri (JSI), 2020)
Speaking is a subject matter that must be learned by the students because it is the most important factor in the development of English language skills. However, it is more difficult than another subject because there are some difficulties experienced by students in speaking, such as low vocabulary mastery, the difficulties in pronouncing, confused in arranging words, afraid of making mistake and many another factors that cause of speaking difficulties such as teaching strategy, the curriculum, and the environment. The research purpose is to know the factors of the students' speaking difficulty. The design of the research is descriptive qualitative. The number of population as many as 157 students of eleventh-grade students of SMA Negeri 2 Tembilahan that consist of 6 classes. In taking the sample, the researcher uses a simple random sampling technique. The number of samples is 40 students or 25% of the population. The researcher uses a questionnaire as an instrument as many as 15 items and also uses an interview technique. After analyzing the data by using the descriptive qualitative method, it is known that the four factors of speaking difficulty have a positive value or more than 50%. The values of these four factors were 62.5% for personal factors, 95% for teaching strategies factor, 90% for curriculum factor and 57.5% for the environmental factor. Therefore, it can be inferred that the dominant factor which causes students’ difficulties in speaking is teaching strategies.